Fish Buying and Selling Practices in the Perspective of Sharia Law and Business (Case Study at the TPI Market in Sumber Jaya Village) - Tia Ica Susanti; Marini Marini; Woolnough Cale (Yayasan Adra Karima Hubbi, 2023)
The title of this research is the practice of buying and selling fish in the perspective of sharia law and business (case study at the TPI market, Sumber Jaya Village). The population in the study took the market head, traders, and buyers. The sample of this research is Bengkulu City TPI market traders. This research is qualitative research, the data analysis method used in this research is qualitative descriptive analysis, where researchers in addition to processing and presenting data, also analyze the qualitative data. The practice of buying and selling fish at the TPI market in Sumber Jaya Village is an indicator of the value of awareness between sellers and buyers respecting each other's rights and obligations. The result of this research identifies an opportunity for the implementation of buying and selling in the perspective of sharia law and business in exchange activities or buying and selling in the TPI market, because the majority of respondents think that it is important to implement buying and selling Islamically or in the perspective of sharia law and business. Although in theory they do not understand it, normatively they implement Islamic business ethics.